Literature Study: Effectiveness of Character Education Programs in Elementary Schools - Rosmiati, Sely; Maftuh, Bunyamin (International Conference on Elementary Education, 2025)
Character education in elementary schools is an important element in forming a generation that is not only academically intelligent, but also has high moral and ethical integrity. This study analyzes the effectiveness of character education programs through literature studies, showing that the success of the program is highly dependent on the involvement of teachers, parents, and the community. Although many programs have been implemented, challenges in their implementation still exist, including teachers’ understanding of character education and limited resources. The habituation method has proven effective in instilling character values in students. However, the gap between theory and practice is still a problem, with many teachers feeling less able to implement the program effectively. To ensure the effectiveness of character education programs, there needs to be measurable boundaries, such as specific indicators that can be used to assess the success of implementation. This study recommends the need for more integrated evaluation and development of character education programs on an ongoing basis to ensure a positive impact on student personality development. It is hoped that the results of this study can make a significant contribution to the development of education policies in Indonesia and create a young generation with good character and responsibility towards society.